MANAJEMEN DAN KEPEMIMPINAN PENDIDIKAN ISLAM: KOLABORASI NILAI ISLAM DAN PRINSIP MANAJEMEN MODERN - Prayogi, Endar Evta Yuda; M. Agus Kurniawan (Jurnal Dinamika Pendidikan Islam, 2026)
The development of global management thought has profoundly influenced educational governance in Islamic institutions. Purpose: This study aims to examine how Islamic leadership values can be integrated with modern management principles in the administration of Islamic educational institutions in Indonesia. Method: The study employed a qualitative approach with a phenomenological design, involving 12 principals and educational managers from Islamic schools and madrasas across three provinces. Data were collected through in-depth interviews, observation, and document analysis. Results: Findings indicate that effective Islamic educational leadership combines prophetic values (shura, amanah, adl) with contemporary management functions (planning, organizing, actuating, controlling), resulting in a distinctive hybrid leadership model that enhances both institutional performance and spiritual culture. Conclusion: The integration of Islamic values and modern management principles is not contradictory but complementary, producing a contextually relevant and spiritually grounded leadership paradigm for Islamic educational institutions.